Review and comparative analysis of strength criteria for modelling non-linear behaviour of concrete - G. I. Rempel; A. M. Budarin; A. P. Dolgikh; A. A. Kamzolkin; V. N. Alekhin (Vestnik MGSU)
Introduction. In recent decades, numerical methods for calculating concrete and reinforced concrete structures have developed significantly, taking into account the physically nonlinear behavior of the material. Such methods, in comparison with analytical ones, make it possible to describe the work of the material more accurately and reflect the main features of its stress–strain state. This makes it possible to perform more cost-effective and, in some cases, more reliable design solutions. Concept of the limit surface plays an important role in numerical methods. Limit surface, which is expressed by a condition (strength criterion), separates the elastic and plastic region of the material. Strength criteria must correspond to experimental data, provide a mathematically stable unique solution, and also have a set of parameters that can be easily determined from empirically based expressions or test data. The history of creation and improvement of concrete limit surfaces includes dozens of domestic and foreign works, many of which do not meet these requirements. The purpose of the current work is a comparative analysis of the most common strength criteria of concrete.Materials and methods. This study is based on the analytical generalization and systematization of the data received form domestic and foreign sources.Results. A detailed analysis of the most common domestic and foreign concrete limit surfaces was carried out.Conclusions. According to the analysis results, the comparison of the concrete limit surfaces was performed.